Perancangan Alat Desalinasi Air Laut Tenaga Surya Tipe Basin Double Slope Kemiringan 45º Dengan Skala Rumah Tangga - Benny Wahyudi; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The problem of meeting the need for clean water has been a challenge in its own right in the last few decades, not only in Indonesia but also around the world. Fulfillment of clean water needs that are not optimal, especially drinking water, causes the community's need for drinking water not to be met. One solution to this problem is to utilize abundant sea water as a source of clean water for coastal communities by first purifying it. This seawater purification method is known as the desalination method, where the desalinated sea water will be separated from salt and other particles. One type of seawater desalination is the basin type, which is by using a reservoir as a container for storing seawater, then seawater. steam it with heat from sunlight so that the salt content and impurities contained in it will be separated completely because of the difference in each evaporation temperature. The design of a desalination device with a target of 8 liters per day of distilled yield, which will be used as consumption water for household needs, is expected to be a solution to this problem. Keywords: Sea Water, Freshwater, Desalination